Case Studies of Costs and Benefits of Non-Tariff Measures Cheese, Shrimp and Flowers - van Tongeren, Frank (OECD Food, Agriculture and Fisheries Papers, 2010)
This report applies a cost-benefit analysis to quantify the economic effects of non-tariff measures in the agri-food sector. Three case studies are presented to demonstrate how such analysis can help identify least-cost solutions of Non-Tariff Measures (NTMs) designed to ensure that imported products meet domestic requirements. The present analysis examines benefits and costs for the different domestic and foreign stakeholders involved, thus taking a broader view that goes beyond evaluating the trade impact alone